Structural and functional analyses of a yeast mitochondrial ribosomal protein homologous to ribosomal protein S15 of Escherichia coli. - Dang, H (1990)
We have purified a small subunit mitochondrial ribosomal protein, MRPS28p, from the yeast, Saccharomyces cerevisiae. Sequence from the amino terminus of MRPS28p was used to design a degenerate oligonucleotide that was complementary to the MRPS28 gene. The MRPS28 gene was isolated and its sequence determined. The MRPS28 sequence encodes a 28 kDa protein that has a region of homology with ribosomal protein S15 of E. coli. This region spans the entire length of the E. coli protein, but as MRPS28p is larger, includes only the portion of the MRPS28p sequence from amino acids 150 to 238. Based on this homology, we predict that MRPS28p, like E. coli S15, interacts directly with small subunit rRNA and functions as an early protein in ribosome assembly. Cells carrying a disrupted chromosomal copy of MRPS28 are unable to respire and spontaneously lose portions of their mitochondrial genomes at a high frequency. These phenotypes are consistent with an essential role for MRPS28p in the assembly and/or function of the mitochondrial ribosome.